PELATIHAN PEMERTAHANAN BAHASA IBU MELALUI PELATIHAN BACA PUISI DAN BERPANTUN DI TK NASYIATUL AISYIYAH MUNGKA KABUPATEN 50 KOTA - Wahyudi Rahmat; Samsiarni Samsiarni; Aruna Laila; Mila Kurnia Sari (LPPM (Institute for Research and Community Services) Universitas Andalas Padang, 2018)
Raising of local language needs to be implemented especially for children. In order to do so, we use reading poetry and poem training for students of TK Nasyiatul Aisyyah Mungka, 50 Kota. With the practice of reading poetry and poem in this Minangkabau language, students of TK Nasyiatul Aisyyah Mungka, 50 Kota will be able to speak and communicate with their local language. Local languages have long been used by many Indonesian authors, both in works of fiction and poetry. It is expected that this method will increase their awareness Of Minangkabau language. They will also appreciate the beauty of the poetry a nd poem in the Minangkabau language